An evaluation of arrangement and description of church records in selected parishes of Cavite towards proposing a system of classification - Dilidili, Analiza P.; Aguirre, Vyva Victoria M.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
Effective management of information allows fast, accurate and reliable access of records; ensures the timely destruction of inactive information and the identification and protection of vital and historically important records (NAS, 2005). The Church is one of the important organizations in the history of every community because it maintains the records of its people. Proper arrangement and description of records are essential to make the information authentic, accurate, accessible, complete and comprehensive.
This study evaluates the arrangement and description of church records in selected parishes of Upland Cavite. Specifically, it: a) identifies and describes the church records that can be classified as archival in selected parishes; b) determines the current status of records management in these parishes; c) identifies the issues and problems encountered in the handling of these church records; and d) recommends a system of classification for these records so that they can be better arranged for easy retrieval historical descriptive method of research with the survey questionnaires as data-gathering instrument was used. Ocular inspections and interviews with the parish priests and parish secretaries were also conducted to gather the necessary information needed for documentary analysis.
The research findings showed that: a) baptismal records, confirmation records, marriage records and burial records are the most important documents of the selected parishes and these are considered permanent because of their historical, evidential, research and informational values; 2) administrative records (e.g., history files, constitution and by-laws, journals/pamphlets, sermons and appointment files of parish priests) and annual financial records are also kept permanently but proper arrangement and preservation of these documents is not the priority of the said parishes; c) finding aids such as accession records and subject indexing are used by the parishes; d) they use labeling, filing and shelving in arrangement of church records; e) the parishes analyze the type and contents of the documents for intellectual activities of arrangement of records; f) due to absence of proper preservation and restoration program, the earliest documents look fragile, deteriorating, have torn pages taped with acidic tape and some pages are found with booklice and termites; g) lack of relevant training and seminars for the parish secretaries resulted in mishandling of records; and h) the parish secretaries are not familiar with the accepted and standard arrangement and description of archival records.
The following recommendations are proposed for implementation: a) a written policy on arrangement and description are necessary to provide for physical and intellectual control of archival records; b) description using ISAD (G) could be adapted to improve the present arrangement and description of records for easy retrieval and access; c) disaster management program and proper restoration program is necessary to preserve the integrity and authenticity of the records; d) relevant training and seminars for parish secretaries are necessary to improve their knowledge of records management practices; and e) the parishes are advised to make use of and build on the inventory list the description of records developed in this study.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Church records and registers -- Philippines -- Cavite; Records -- Philippines -- Cavite -- Management